Baseline chest radiographic findings among HIV positive adults in a poor resource economy - Umar, Faruk Kabir; Saidu, Sule Ahmed; Ma'aji, Sadisu; Danfulani, Muhammad; Yunusa, Garba Haruna; Gele, Ibrahim Haruna; Hafsat, Akininibosun Raji; Joshua, Garba A; Amin, Halimat Hassan; Mohammed, Yahaya (Asian Journal of Medical Sciences, 2021)
Background: Human Immunodeficiency Virus (HIV) infection has been known to pose one of the most formidable challenges to progress and development. It is a public health burden associated with high morbidity. Chest radiograph is an important tool in manifesting some of the findings associated with HIV. Aims and Objectives: To determine the baseline chest radiographic findings among HIV positive adults in a poor resource economy. Materials and Methods: 140 Newly diagnosed adult HIV positive, HAART naïve, participants were recruited in the Radiology Department of Usmanu Danfodiyo University Teaching Hospital (UDUTH) Sokoto and had their chest radiograph done using Silhoutte VR System GE diagnostic x-ray equipment. The processed radiographs were viewed using an illuminated viewing box and then reported by the investigator and cross-checked by another consultant Radiologist. Data collated was analysed using SPSS version 23. Results: The study showed female to male ratio of 2.2: 1. Normal chest radiographic finding was found in 67(47.9%) participants. Pulmonary consolidation 32 (22.9%) constituted the highest abnormal chest finding. The least of the abnormal radiographic findings were emphysematous bullae 1(0.7%) and plate atelectasis 1(0.7%). Majority of the lesions were in the upper zone, 43(30.7%) and on the right side. Conclusion: The study provides baseline data on the chest radiographic patterns among the HAART naïve HIV positive adult patients in a poor resource economy.